Ciągłość i zmiana, czyli fenomen monarchii brytyjskiej - Tulejski, Tomasz (PRAWO i WIĘŹ, 2026)
This essay examines the British monarchy as a unique institution that has endured for centuries by balancing tradition with adaptation, maintaining a significant role in the UK’s political and social system. It begins by contextualizing European monarchies, noting their political marginalization in the democratic era, where monarchs must adapt to the “will of the people” to survive. The British monarchy stands out for its adaptability, rooted in the flexibility of the UK’s unwritten constitution, which blends historical continuity with dynamic evolution. Drawing on thinkers like Edmund Burke, Walter Bagehot, David Cannadine, Vernon Bogdanor, and Martin Loughlin, the essay explores the monarchy’s evolution from a divinely sanctioned institution to a symbol of national identity and democratic legitimacy. Burke highlights the constitution’s organic development, Bagehot distinguishes its “dignified” and “efficient” roles, and modern scholars like Bogdanor emphasize the monarchy’s neutral role in democracy. Cannadine underscores its ability to create unifying rituals, particularly in the imperial and post-colonial eras. The essay also addresses contemporary challenges, such as lower support among younger generations and ethnic minorities and its role in the Commonwealth. It argues that the monarchy’s success lies in its ability to balance conservatism and modernism, ensuring its relevance in a changing world. The conclusion suggests that the monarchy’s future hinges on continued adaptation, especially amid demographic shifts and potential republican sentiments.